EARTH SCIENCE APPLICATIONS IN THE FIELD OF ARCHAEOLOGY: THE HELIKE EXAMPLE - Katsonopoulou, Dora (Bulletin of the Geological Society of Greece, 2010)
Earth science applications are widely used in the field of archaeology today. The Helike Project made use of such applications at a time when archaeology in Greece was mostly limited to traditional methodology only. Thus Helike constitutes a pioneer study case of such investigations and of their usefulness in the field of archaeology. In searching for Ancient Helike, our team since 1988 combined extensively traditional archaeological research methods and geophysical and geological exploration. The results of this multidisciplinary approach were in most cases successful beyond expectations. In this paper, I present and discuss the most significant archaeological discoveries in the area of Helike based primarily on data from our geological and geophysical investigations the last 20 years.